The social and economic reality of Iraqi women and its impact on their societal role for the period (1921-2003) - Assist Prof.Dr Ammar Saadoun Salman; Saja Ahmed Qasim (The college of law and political science journal, 2024)
The research aims to study the social and economic reality of women in Iraq for the period 1921-2003 in light of the political transformations that accompanied the Iraqi political system. The research also aims to study the extent to which political, social and economic challenges have contributed to limiting women’s participation in political work. Women’s political participation is evidence of society’s awareness of itself and its civilization. Political participation is a cultural phenomenon as well as a political phenomenon. When society reaches a certain stage of sophistication and progress, the issue of women’s political participation becomes one of its fundamental issues. The research concludes that the phenomenon of limited political participation of Iraqi women and the extent of the influence of the social and economic factor on women’s participation in political life in Iraq is the result of many interacting and overlapping factors at the general societal level, whether political, economic or social.